Fairness and rights in international criminal procedure - Rigney, Sophie (Edinburgh : Edinburgh University Press, 2022)
Through an in-depth critical analysis of procedural decisions at the ICTY and ICC between 2008 and 2018, Rigney shows that there is a clear separation between fairness and rights in practice. She demonstrates tthat fairness is invoked in international criminal law decisions in inconsistent ways that are frequently at odds with defendants' rights.
Frontmatter -- Contents -- Acknowledgements -- Introduction: Why fairness and rights matter, and what this book sets out to do -- 1 The particular place of international criminal trials: aims and procedure -- 2 The centrality of rights and fairness in international criminal trials -- 3 The incoherence of fairness in international criminal trials -- 4 Fairness, the rights of the accused and disclosure -- 5 Fairness, the rights of the accused and the use of adjudicated facts -- 6 Fairness, the rights of the accused and the protection of witnesses -- Conclusions: Closing the space between fairness and rights, and reimaging the future of international criminal law -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Criminal procedure (International law); International criminal courts; Procédure pénale (Droit international); Tribunaux pénaux internationaux; LAW / Courts; Criminal procedure (International law); International criminal courts; Electronic books; Electronic books